Association of Intensive Lifestyle and Metformin Interventions With Frailty in the Diabetes Prevention Program Outcomes Study. (11th January 2021) - Hazuda, Helen P; Pan, Qing; Florez, Hermes; Luchsinger, José A; Crandall, Jill P; Venditti, Elizabeth M; Golden, Sherita H; Kriska, Andrea M; Bray, George A
Abstract: Background: Frailty is a geriatric syndrome of decreased physiologic reserve and resistance to stressors that results in increased vulnerability to adverse health outcomes with aging. Diabetes and hyperglycemia are established risk factors for frailty. We sought to examine whether the odds of frailty among individuals at high risk of diabetes randomized to treatment with intensive lifestyle (ILS), metformin, or placebo differed after long-term follow-up. Method: The sample comprised participants in the Diabetes Prevention Program (DPP) clinical trial, who continued follow-up in the DPP Outcomes Study (DPPOS) and completed frailty assessments in DPPOS Years 8 ( n = 2385) and 10 ( n = 2289), approximately 12 and 14 years after DPP randomization. Frailty was classified using Fried Frailty Phenotype criteria. GEE models adjusting for visit year with repeated measures pooled for Years 8 and 10 were used to estimate pairwise odds ratios (ORs) between ILS, metformin, and placebo for the outcomes of frail and prefrail versus nonfrail. Results: Frailty prevalence by treatment group was ILS = 3.0%, metformin = 5.4%, placebo = 5.7% at Year 8, and ILS = 3.6%, metformin = 5.3%, placebo = 5.4% at Year 10. Odds ratios (95% CI) estimated with GEE models were ILS versus placebo, 0.62 (0.42–0.93), p = .022; metformin versus placebo, 0.99 (0.69–1.42), p = .976; and ILS versus metformin, 0.63 (0.42–0.94), p = .022. Odds of being frail versus nonfrail were 37% lower for ILS compared to metformin and placebo. Conclusions: Early ILS intervention, at an average age of about 50 years, in persons at high risk of diabetes may reduce frailty prevalence in later life. Metformin may be ineffective in reducing frailty prevalence. Clinical Trials Registration Numbers: NCT00004992 (DPP) and NCT00038727 (DPPOS).